2017
DOI: 10.4236/jsea.2017.108038
|View full text |Cite
|
Sign up to set email alerts
|

The ISBSG Software Project Repository: An Analysis from Six Sigma Measurement Perspective for Software Defect Estimation

Abstract: The International Software Benchmarking Standards Group (ISBSG) provides to researchers and practitioners a repository of software projects' data that has been used to date mostly for benchmarking and project estimation purposes, but rarely for software defects analysis. Sigma, in statistics, measures how far a process deviates from its goal. Six Sigma focuses on reducing variations within processes, because such variations may lead to an inconsistency in achieving projects' specifications which represent "def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Measure Phase is to understand current baseline performance of key variables. [26] explained measure phase is the phase for data collection development to determine issues and shortfalls. Analyze phase is the stage to evaluate the process variations, to perform root cause analysis and prioritize opportunity of improvements.…”
Section: Lean Six Sigma: Principle and Methodsmentioning
confidence: 99%
“…Measure Phase is to understand current baseline performance of key variables. [26] explained measure phase is the phase for data collection development to determine issues and shortfalls. Analyze phase is the stage to evaluate the process variations, to perform root cause analysis and prioritize opportunity of improvements.…”
Section: Lean Six Sigma: Principle and Methodsmentioning
confidence: 99%
“…In 2017, Almakadmeh et al [23] analyzed the ISBSG MS-Excel based dataset on Six Sigma measurements and found that the ISBSG dataset has a high ratio of missing data within the data fields of the "Total Number of Defects" variable. They identified that this missing ratio represents a serious challenge when the ISBSG dataset is being used for software defect estimation.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Evaluation models based on characteristic parameter tracking methods have been introduced to predict equipment operation states. This involves fitting observed data linearly to obtain characteristic parameter values, thus establishing a quantitative relationship between equipment states and detection periods [9][10].…”
Section: Advancements In Lightning Protection and Operation State Eva...mentioning
confidence: 99%
“…At present, it is a very common phenomenon to use robots as auxiliary production tools in all kinds of substations, which can alleviate the heavy problem of substation inspection work to a certain extent. Safety is the core requirement of substation, which is dangerous under high voltage [9]. In order to ensure the safety of pedestrians and equipment, it is necessary to effectively detect pedestrians according to the monitoring video near the substation.…”
Section: Substation 311 Development Of Substation Inspectionmentioning
confidence: 99%